74 Teaching ethics within palliative care: Identifying priority topics and preferred learning styles. (14th March 2023) - Schofield, Guy; Nakiganda, Harriet; Brangan, Emer; Acuda, Wilson; Huxtable, Richard; Selman, Lucy E
Abstract : Background: There are multiple approaches to teaching clinical ethics in palliative care. What is not clear are the preferences of on-the-ground specialist palliative care providers (SPCPs) regarding which ethics topics to prioritise and the teaching methods to use. Understanding these is crucial in ensuring training programmes and continuing professional development (CPD) are focused, effective, and relevant to time-pressed professionals. Aim: To explore SPCPs' priorities for ethics training topics and preferred methods of teaching delivery Methods: As part of a larger project exploring ethical challenges facing SPCPs in Uganda, we conducted semi-structured interviews with staff in Uganda, exploring their views about priority ethics topics for teaching and preferred teaching methods. Results: 36 participants (17 nurses, 8 physicians, 5 clinical officers, 6 social workers) were interviewed across 7 clinical sites. 11 knowledge areas were prioritised: autonomy, goals of care, confidentiality, nature of ethics and ethical theories, justice, beneficence, truth telling and collusion, non-maleficence, philosophy of palliative care, professional ethics, and euthanasia. Participants also described five skills as important to learn: communication skills; how to approach and manage ethical challenges; self-care for moral distress; understanding one own's ethical biases; and advocacy skills. Five teaching methods were preferred, in order: real-life case group discussion, simulated case group discussion, roleplay, lectures, and clinical placement with an ethical focus. Conclusion: The topics prioritised by SPCPs in Uganda covered a broader range of ethical challenges than is usually included in current training materials. Participants wanted not only ethical knowledge-based training, but also skills training, including self-care related to the moral distress of difficult ethical decision-making. Participants preferred learning via case discussions to lectures or clinical placements. No current comparable data exists for the UK or Irish setting, and these results should be used to spur debate on this subject in these areas.